Identification and Validation of Acromegaly Quality of Life Questionnaire (AcroQoL) for Colombian Population (2024)
ABSTRACT: Introduction: Acromegaly is a rare disease caused by a pituitary adenoma in most cases. Physical changes, metabolic disturbances, osteoarticular symptoms, as well as psychological and social repercussions reduce the Quality of Life (QoL) of people suffering from the disease. Objective: To asses both generic and disease-specific instruments employed to capture the influence of acromegaly on patients’ QoL. Methods and analysis: This scoping review assessed the different tools used to evaluate QoL in people with acromegaly. This review followed the methods proposed by the Joanna Briggs Institute and is reported following the Preferred Reporting Items for Systematic Reviews manual and Meta-Analyses extension for Scoping Reviews. Results: Of a total of 198 studies, 30 questionnaires were identified and categorized by type (specific or generic) and number of domains assessed (physical health, psychological state, autonomy, and social relationships). Among these, 3 were specific-multidomain, 18 generic-multidomain, 3 specific-unidomain, 5 generic-unidomain, and only 1 had no domains. All were patient-reported outcome measures (PROM) used in various contexts. Optimal instruments were disease-specific, multidimensional, brief, easily administered, available in multiple languages, with psychometric validation in acromegaly patients and cross-cultural validation, and assessing treatment impact on QoL. Conclusions: This review explores the use of PROMs in assessing HRQoL in acromegaly patients, emphasizing the need for specific, validated, and culturally adapted tools addressing symptoms and treatment impact. We propose a novel domain-based classification to overcome existing limitations of instruments and improve their presentation in future studies. This study provides a synthesis that helps advance research and guide clinical practices around HRQoL in acromegaly management.